The Effect of Vitamin D Supplementation on Recurrence-Free Survival in Melanoma Patients: A Systematic Review and Meta-Analysis - Aldila Ardine; Raisa Khairuni (The International Journal of Medical Science and Health Research, 2026)
Introduction: Vitamin D has been proposed as a potential adjunctive therapy in melanoma based on its biological effects on tumor cells and immune modulation. However, the clinical benefit of vitamin D supplementation in reducing melanoma recurrence or progression remains uncertain. Objective: To systematically evaluate the impact of vitamin D supplementation on recurrence-free survival in patients with melanoma. Methods: A systematic review and meta-analysis were conducted according to PRISMA guidelines. Eligible studies included randomized controlled trials and cohort studies comparing vitamin D supplementation to placebo or no supplementation in melanoma patients and reporting recurrence-free, disease-free, or progression-free survival. Data were synthesized using a random-effects model, and hazard ratios (HRs) were pooled. Results: Three studies (n=739) were included, encompassing both adjuvant and advanced melanoma settings. The pooled analysis demonstrated no statistically significant association between vitamin D supplementation and improved recurrence-free survival (HR 0.83, 95% CI: 0.52–1.32; p = 0.43). Moderate heterogeneity was observed. Only one study, involving patients treated with anti–PD-1 immunotherapy, showed a significant benefit, whereas randomized trials in the adjuvant setting did not. Discussion: Although preclinical and observational data support a potential role for vitamin D in melanoma, clinical trial evidence does not demonstrate a significant effect on recurrence-free survival. Heterogeneity in study populations, supplementation regimens, and timing may influence outcomes. Conclusion: Vitamin D supplementation cannot currently be recommended solely to prevent recurrence or progression in melanoma, but remains important for general health. Further research, particularly in the context of immunotherapy, is warranted.